Partisipasi Masyarakat Dalam Penegakan Hukum Terkait Perlindungan Satwa Di Indonesia - Marsya Razita Nur Sabrina; Mira Aurelita; Syanaya Karina Hanum; Marsha Aulia Dwimahendra; Audrey Azka Bilqis; Melian Sahara; Mulyadi Mulyadi (Institut Nalanda, 2023)
Indonesia is one of the most biodiverse countries in the world with a wide variety of animals spread from Sabang to Merauke. The number of animals owned, not a few of these animals become victims of human crimes. The existence of regulations cannot be used as a benchmark. Weak law enforcement indirectly makes people underestimate and do not care about animal welfare in human life. This research aims to find out the right steps so that people are aware of the importance of animal protection and examine the applicable rules regarding the sanctions imposed, as well as cooperation efforts between the government as a supervisor and lawmaker with the community as a participant in animal protection in Indonesia. This research uses a normative legal research method using a statutory approach, so that by using this method, researchers can describe the data as a whole and clearly in accordance with field conditions. The results show that there are still a lot of cruel behaviors committed by humans against animals, even to the point of threatening the animal population. The obstacle in handling cases is the low level of public awareness which impacts on the lack of participation in animal protection. The lack of participation is caused by the lack of education to the community, and the regulations applied do not have sanctions that have a deterrent effect on the perpetrators. Therefore, efforts are needed in the form of continuous socialization to the community and the involvement of all parties, both government and society, in dealing with the problem thoroughly and firmly on cases that occur in accordance with applicable regulations and provide a deterrent effect to animal criminals